Superior temporal sulcus and social cognition in dangerous drivers - Zelinková, Jana; Shaw, Daniel Joel; Mareček, Radek; Mikl, Michal; Urbánek, Tomáš; Peterková, Lenka; Zámečník, Petr; Brázdil, Milan (NeuroImage, 2013)
Understanding the neural systems underpinning social cognition is a primary focus of contemporary social neuroscience. Using functional magnetic resonance imaging (fMRI), the present study asked if brain activity reflecting socio-cognitive processes differs between individuals according to their social behavior; namely, between a group of drivers with frequent traffic offenses and a group with none. Socio-cognitive processing was elicited by employing videos from a traffic awareness campaign, consisting of reckless and anti-social driving behavior ending in tragic consequences, and control videos with analogous driving themes but without such catastrophic endings. We investigated whether relative increases in brain function during the observation of these campaign stimuli compared with control videos differed between these two groups. To develop the results of our previous study we focused our analyses on superior temporal sulcus/gyrus (STS/STG). This revealed a bigger increase in brain activity within this region during the campaign stimuli in safe compared with dangerous drivers. Furthermore, by thematically coding drivers' verbal descriptions of the stimuli, we also demonstrate differences in STS reactivity according to drivers' scores on two indices of socio-cognitive processing: subjects' perceived consequences of actors' actions, and their affective evaluation of the clips. Our results demonstrate the influence of social behavior and socio-cognitive processing on STS reactivity to social stimuli, developing considerably our understanding of the role of this region in social cognition.
Keywords: Young Adult; STS; Social Behavior; mapování mozku; dopravní nehody; Antisocial behavior; Male; řízení motorových vozidel; magnetická rezonanční tomografie; mladý dospělý; Accidents, Traffic; Temporal Lobe; spánkový lalok; Road safety campaign videos; Adult; Image Processing, Computer-Assisted; dospělí; Social cognition; mužské pohlaví; Automobile Driving; počítačové zpracování obrazu; Brain Mapping; lidé; Humans; fMRI; sociální chování; Magnetic Resonance Imaging